Relationships between task awareness, comprehension strategies, and literacy outcomes - Higgs, Karyn P.; Santuzzi, Alecia M.; Gibson, Cody; Kopatich, Ryan D.; Feller, Daniel P.; Magliano, Joseph P. (Frontiers in Psychology, 2023)
The present study tested the Task Awareness Mediation Hypothesis. This hypothesis assumes that the strategies that support comprehension (paraphrasing, bridging and elaborative strategies) positively affect readers’ task awareness while engaged in a literacy task. Moreover, the level of task awareness partially mediates the relationship between comprehension strategies and a comprehension outcome. Across two different time points in a semester, college students were administered an assessment of their propensity to engage comprehension strategies. They were also administered a complex academic literacy task and responded to an open-ended question during the task that provided an assessment of task awareness. Indirect effects analyses provided evidence for the Task Awareness Mediation Hypothesis and showed that the propensity to engage in comprehension strategies was positively predictive of task awareness, and task awareness mediated the relationships between comprehension strategies and performance on the complex academic literacy task. These results suggest that task awareness is related to performance because it helps explain how comprehension strategies support performance in complex academic literacy tasks.